Everyday life in a Swedish nursing home during the COVID-19 pandemic: a qualitative interview study with persons 85 to 100 years. Issue 6 (18th June 2021) - Lood, Qarin; Haak, Maria; Dahlin-Ivanoff, Synneve
Abstract : Objective: To understand and report on the impact of the COVID-19 pandemic on the everyday lives of frail older persons living in nursing homes by exploring their experiences of how the pandemic-related restrictions had influenced them and in what way. Design: Empirical qualitative interview study. Setting: A publicly run nursing home in an urban area in Sweden in June 2020. The nursing home had visitor restrictions, cancelled activities and physical distancing requirements since March 2020. Participants: A total of 10 persons, 85–100 years, living in a Swedish nursing home during the COVID-19 pandemic, were recruited through nursing home management and interviewed in June 2020 using medically approved visors and physical distancing. Analysis: Interviews were analysed using thematic analysis, which involves familiarisation, coding and definition of themes. Transcripts were coded into data-driven categories before being organised into categories that described and explained the data. Results: The analysis resulted in the main theme 'It is like living in a bubble', that describes everyday life in the nursing home during the pandemic as a world of its own in which the older persons felt both protected and isolated. This is described in four subthemes: living 1 day at a time, without fear of the virus; feeling taken care of; having limited freedom and missing out on the little extras. Conclusions: Contributing to the growing area of COVID-19-related research, our findings provide novel insights into how pandemic-related restrictions in nursing homes represent a risk of isolating older people from the outside world and diminishing their freedom. Put in relation to the previous research, these findings could be applied beyond the pandemic, to develop research and practice that puts focus on how to support older people to decide for themselves how to spend the rest of their lives.